Perancangan Interior Fashion Lounge & Bar Di Surabaya - Jiemesha, Hilda; Mulyono, Grace (Intra, 2014)
The rapid growth of lifestyle in big city especially Surabaya encourage the needs of good places, like Lounge & Bar for young executives and entrepreneurs who seek a well-organized yet trendy place to build a social relation. They love places which offer a well design interior space as well as great ambiance for doing business with pleasure. The design of Lounge & Bar also stress on the importance of fashion trends, hence it is suitable as a place to held fashion runway. The design of Lounge and Bar for young fashionable executive has to haveÂ a unique characterÂ and contribute to the creation ofÂ the interiorÂ which accommodates completeÂ servicesÂ as requested, such as stage, bar area, lounge area, and also divider arrangement. In order to emerge glamour ambiences in luxurious fashion, exclusive andÂ uniqueÂ as a â€œone of a kindâ€, Lounge and Bar uses the exclusive concept of â€œCrystallizeâ€.